2008
DOI: 10.1593/neo.81078
|View full text |Cite
|
Sign up to set email alerts
|

Bmi1 Is Required for Hedgehog Pathway-Driven Medulloblastoma Expansion

Abstract: Inappropriate Hedgehog (Hh) signaling underlies development of a subset of medulloblastomas, and tumors with elevated HH signaling activity express the stem cell self-renewal gene BMI1. To test whether Bmi1 is required for Hh-driven medulloblastoma development, we varied Bmi1 gene dosage in transgenic mice expressing an oncogenic Hh effector, SmoA1, driven by a glial fibrillary acidic protein (GFAP) promoter. Whereas 100% of SmoA1; Bmi1(+/+) or SmoA1;Bmi1(+/-) mice examined between postnatal (P) days 14 and 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 21 publications
2
49
0
Order By: Relevance
“…Nevertheless, the pattern of lineage markers, robust proliferation, and occasional areas of central necrosis seen in GLI2ΔN-expressing tumors described in this report are in keeping with the diagnosis of nodular, BCC-like tumors. Interestingly, the weak transforming potential of activated Smo alleles may be limited to skin, since Smo is a potent oncogene in cerebellum, where it gives rise to medulloblastomas with high penetrance when targeted to neuronal progenitors (50,61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the pattern of lineage markers, robust proliferation, and occasional areas of central necrosis seen in GLI2ΔN-expressing tumors described in this report are in keeping with the diagnosis of nodular, BCC-like tumors. Interestingly, the weak transforming potential of activated Smo alleles may be limited to skin, since Smo is a potent oncogene in cerebellum, where it gives rise to medulloblastomas with high penetrance when targeted to neuronal progenitors (50,61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Medulloblastoma, a primitive neuroectodermal tumor, is thought to arise from immature neural progenitors in the cerebellum (Lee et al, 2005). Genomic alterations in components of the Hh signaling pathway have been identified in up to 25% of human medulloblastomas (Michael et al, 2008), consisting of inactivating mutations of Ptch1 and Sufu and/or activating mutations of Smo (Taylor et al, 2002;Hallahan et al, 2004;Oliver et al, 2005;Mao et al, 2006;Thomas et al, 2009;Huse and Holland, 2010). More recently, dysregulated Hh signaling has been shown to be sufficient to generate tumors in either neural stem cell (NSC) or precursor cell populations, implicating a more primitive cell of origin (Schuller et al, 2008;Yang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This gene is implicated in the pathogenesis of brain tumors such as glioma (Bruggeman et al, 2007) and medulloblastoma (Leung et al, 2004;Wiederschain et al, 2007;Michael et al, 2008), and is an important epigenetic regulator of fate determination and proliferation in stem cell populations (Valk-Lingbeek et al, 2004;Bracken et al, 2006). Previous reports have suggested that there is a potential link between Hh signaling and Bmi1, alluding to a novel regulatory mechanism whereby an external signaling morphogen interacts with cell-intrinsic epigenetic pathways controlling cell fate programs (Valk-Lingbeek et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of BMI1 is observed in 30-40% of MBs, resulting in inhibition of apoptotic pathways through sups, resulting in inhibition of apoptotic pathways through suppression of p16ink4a and p19arf [31]. Similar to what is described by Flora et al for Math1 [17], deletion of Bmi1 in a medulloblastoma mouse model driven by activated Smo (SmoA1) completely abrogates tumorigenesis [31].…”
Section: Bmi1mentioning
confidence: 67%